Vaccine sero-monitoring and sero-surveillance of Peste des petits ruminants in small ruminants in West Gojjam zone, Amhara region, Ethiopia - Mandefro, Mesafint; Ibrahim, Saddam Mohammed; Sibhatu, Demeke; Kassa, Nebiyou; Emiyu, Kemal; Debebe, Kebede; Dessalegn, Bereket; Birhan, Mastewal; Bitew, Molalegne (Frontiers in Veterinary Science, 2024)
BackgroundPeste des petits ruminants (PPR) is an acute or subacute, highly contagious, and economically important, transboundary disease of small ruminants caused by Peste des petits ruminants virus (PPRV).ObjectivesThe objective of this study was to determine the seroconversion rate in PPR vaccinated flock of sheep (Sekela district) and the seroprevalence of PPRV in unvaccinated flocks of sheep and goats (Yilmanadensa district).MethodsA cross-sectional study was conducted from January to March 2022 in two selected districts of West Gojjam zone, Ethiopia. Multistage cluster sampling was used to select sampling units by successively selecting districts, kebeles, and villages purposively based on their accessibility and vaccination status. Individual animals were selected haphazardly mimicking simple random sampling. Accordingly, a total of 660 blood samples were collected. Out of this, 300 sheep were vaccinated 4 months prior to sampling using the Nigerian 75/1 strain-based freeze-dried live attenuated PPR vaccine and 360 small ruminants (288 sheep and 72 goats) were unvaccinated and assayed for anti-PPRV antibodies using commercial c-ELISA.ResultsThe post-vaccination herd immunity was 76.66% (95% CI: 71.46–81.34), which is slightly lower than the threshold herd immunity recommended by the PPR global control and eradication strategy, which is set to be 80%, to efficiently break the epidemiological cycle of the virus. Seroprevalence of PPRV in unvaccinated sheep and goats was 3.61% (95% CI: 1.94–6.1), indicating the possible circulation of PPRV in the area. Although small ruminants develop solid immunity following natural infection in endemic countries, the infection of naïve animals allows continuous circulation of the virus.ConclusionsIn light of the accumulating evidence of low post-vaccination herd immunity in small ruminants in Ethiopia, the undergoing PPR vaccination strategy needs to be reevaluated to achieve the desired herd immunity at any time ultimately aiding the eradication goal by 2030.